Coping Strategies of Teachers and Students in Addressing Teaching-Learning Challenges Within the Semester System at Mid-West University - Khatri, Ramesh (NPRC Journal of Multidisciplinary Research, 2026)
Background: The semester system, with its emphasis on continuous student assessment and learner-centred approaches, is the most widely used in higher education institutions worldwide. In Nepal, the semester system was introduced in the 1970s at Tribhuvan University, and many other universities, including Mid-West University, have since adopted it from the outset. However, little is known about the challenges encountered in its implementation in newly formed public universities in Nepal, particularly in remote regions. Objective: This study aims to explore the challenges encountered and coping strategies adopted in implementing the semester system at Mid-West University, Surkhet, Nepal, with the aim of contributing to the development of the educational system. Methods: This study used the narrative research method, in which five teachers and five students from five different graduate schools, including the Management, Humanities and Social Sciences, Education, Science and Technology, and Engineering, were selected through the purposeful sampling method. In-depth interviews were used as the primary means of data collection in November 2021, and the data were analyzed using Braun and Clarke’s six-phase thematic analysis. Findings: Five themes were identified, including curriculum-practice mismatch, infrastructure and resource constraints, ICT skills, time pressure, and adaptive self-reliance. Conclusion: This study concluded that implementing the semester system smoothly is affected by various challenges, including curriculum, infrastructure, technology, and assessment load, which need to be addressed in the overall development of the educational system. Novelty: This is the first study to explore the challenges of implementing the semester system and the coping strategies used to address them at Mid-West University, Nepal, in the Karnali province.